The Perspective of Forestry Graduates Toward Rural Forestry Based Business - Anita Hafsari; Bahruni Bahruni; Dudung Darusman (Institut Pertanian Bogor (IPB University), 2015)
The rural forestry business had shown a good economic feasibilty and worthed to develop in the rural economy. However the business income cannot to improve the standard of living worthy and have a low attractiveness. The attractiveness increase can be done with increasing profitability of rural forestry business and enhance the role of forestry graduates. Forestry graduates in Indonesia, with their title as Sarjana Kehutanan (S.Hut) had been scarcely involved in rural and traditional forestry based business. Such anomaly had not been becoming neither governmental nor profesional concerns. This study tried to explore the perspective of the S.Hut, concerning their understanding and interest in the business, to see how far their potential capacity to be entrepreneurs. This study differentiated the respondences into S.Hut working in forestry and S.Hut working in non-forestry job. With qualitative and quantitative approach, and total respondents of 158 persons, consisting 122 persons as forestry jobs and 38 persons as non-forestry jobs, this study found out that the S.Hut in Indonesia had ample or good perspectives based on the parameters of higher interests, attractiveness, knowledge, and effications. It meant that they were worthed to be involved as the business entrepreneurs.